Download presentation

Presentation is loading. Please wait.

Published byAbigail Richard Modified over 6 years ago

1
Solving Systems of Equations By Elimination

2
Warm – up!! *As you walk in, please pick up your calculator!!* Use substitution to solve the following systems of equations. 1. x – 3 = y 2y + 7x = 4 2. 6x -8 = 3y 18 = 7y + 4x

3
Solving Systems of Equations So far, we have solved systems using graphing and substitution. Today we are adding another tool to our toolbox called ELIMINATION. Our goal for elimination is to cancel out one of our variables so that we only have one variable left to solve for.

4
Solving a system of equations by elimination. Step 1: Put the equations in Standard Form. Step 2: Determine which variable to eliminate. Step 3: Eliminate the variable and solve. Step 4: Plug back in to find the other variable. Step 5: Check your solution. Standard Form: Ax + By = C Look for variables that have the same coefficient. Solve for the variable. Substitute the value of the variable into the equation. Substitute your ordered pair into BOTH equations.

5
1) Solve the system using elimination. 2x + 2y = 6 3x – 2y = 4 Step 1: Put the equations in Standard Form. Step 2: Determine which variable to eliminate. They already are! Look at my ys! What coefficients do they both have?

6
1) Solve the system using elimination. Step 4: Plug back in to find the other variable. 2(2) + 2y = 6 4 + 2y = 6 2y = 2 y = 1 2x + 2y = 6 3x – 2y = 4 Step 3: Eliminate the variable and solve. 2x + 2y = 6 3x – 2y = 4 5x = 10 x = 2 2x + 2y = 6 (+) 3x – 2y = 4

7
1) Solve the system using elimination. Step 5: Check your solution. (2, 1) 2(2) + 2(1) = 6 3(2) - 2(1) = 4 2x + 2y = 6 3x – 2y = 4 A great way to know if you have the right answer!!

8
2) Solve the system using elimination. -4x + 4y = 7 4x – 3y = 9 Step 1: Put the equations in Standard Form. They already are! Step 2: Determine which variable to eliminate. Which variable has the same coefficient?

9
2) Solve the system using elimination. -4x + 4y = 15 4x – 3y = 9 Step 4: Plug back in to find the other variable. x + 4(2) = 7 x + 8 = 7 x = -1 Eliminate one of the variables! -4x + 4y = 15 4x – 3y = 9 y = 2 -4x + 4y = 15 (+) 4x – 3y = 9 12y = 24 Step 3: Multiply the equations and solve.

10
-4x + 4y = 15 4x – 3y = 9 2) Solve the system using elimination. Step 5: Check your solution. (-1, 2) -4(-1) + 4(2) =15 4(-1) - 3(2) = 9

11
What is the first step when solving with elimination? Plug numbers into the equation. Add or subtract the equations. Solve for a variable. Check your answer. Determine which variable to eliminate. Put the equations in standard form. Put the steps of solving by elimination in order!!

12
Which variable is easier to eliminate? 3x - 4y = 4 4x + 4y = 6 1. x 2. y 3. 6 4. 4

13
3) Solve the system using elimination. 3x + 7y = -28 4x – 7y = 7 Step 1: Put the equations in Standard Form. They already are! Step 2: Determine which variable to eliminate. You try!! What variable is easiest to eliminate?

14
3x + 7y = -28 4x – 7y = 7 3) Solve the system using elimination. Step 4: Plug back in to find the other variable. 3(-3) + 7y = -28 -9 + 7y = -28 7y = -37 y = -37/7 Step 3: Multiply the equations and solve. Eliminate a variable!!!! 3x + 7y = -28 4x – 7y = 7 x = - 3 3x + 7y = -28 (+) 4x – 7y = 7 7x = -21

15
3x + 7y = -28 4x – 7y = 7 3) Solve the system using elimination. Step 5: Check your solution. (-3, -37/7) 3(-3) + 7(-37/7) = -28 4(-3) - 7(-37/7) = 7

16
Solve using elimination. 2x – 3y = 1 -2x - 4y = 6 1. (2, 1) 2. (1, -2) 3. (5, 3) 4. (-1, -1) You try!!

Similar presentations

© 2022 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google